Metatranscriptomic Sequencing of Sheath Blight-Associated Isolates of Rhizoctonia solani Revealed Multi-Infection by Diverse Groups of RNA Viruses - Urzo, Michael Louie R.; Guinto, Timothy D.; Eusebio-Cope, Ana; Budot, Bernard O.; Yanoria, Mary Jeanie T.; Jonson, Gilda B.; Arakawa, Masao; Kondō, Hideki; Suzuki, Nobuhiro (MDPI, 2024)
Rice sheath blight, caused by the soil-borne fungus Rhizoctonia solani (teleomorph: Thanatephorus cucumeris, Basidiomycota), is one of the most devastating phytopathogenic fungal diseases and causes yield loss. Here, we report on a very high prevalence (100%) of potential virus-associated double-stranded RNA (dsRNA) elements for a collection of 39 fungal strains of R. solani from the rice sheath blight samples from at least four major rice-growing areas in the Philippines and a reference isolate from the International Rice Research Institute, showing different colony phenotypes. Their dsRNA profiles suggested the presence of multiple viral infections among these Philippine R. solani populations. Using next-generation sequencing, the viral sequences of the three representative R. solani strains (Ilo-Rs-6, Tar-Rs-3, and Tar-Rs-5) from different rice-growing areas revealed the presence of at least 36 viruses or virus-like agents, with the Tar-Rs-3 strain harboring the largest number of viruses (at least 20 in total). These mycoviruses or their candidates are believed to have single-stranded RNA or dsRNA genomes and they belong to or are associated with the orders Martellivirales, Hepelivirales, Durnavirales, Cryppavirales, Ourlivirales, and Ghabrivirales based on their coding-complete RNA-dependent RNA polymerase sequences. The complete genome sequences of two novel RNA viruses belonging to the proposed family Phlegiviridae and family Mitoviridae were determined.